THE EXONERATION CLAUSES IN PARKING PRACTICES: A REVIEW FROM THE PRINCIPLE OF PROPORTIONALITY AND INCLUSIVE LAW - Simbolon, Herbert Petrus Wiro; Kurniawan, I Gede Agus (LPPM STIH Putri Maharaja, 2023)
This research focuses on the analysis of exoneration clauses in parking practices from the perspective of proportionality and inclusive law perspectives. This research is a normative legal research with a concept, case, and statutory approach. The results of the study confirm that exoneration clauses in parking practices are usually not in accordance with the principle of proportionality because they ignore the substance in various court decisions where one of the substances is the exoneration clause should not be a means to